2020
DOI: 10.1021/acsami.0c13197
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Hypoxia-Induced Conductive Hydrogel to Promote Diabetic Wound Healing

Abstract: Injectable hydrogels with the capability to cast a hypoxic microenvironment is of great potentialities to develop novel therapies for tissue regeneration. However, the relative research still remains at the conceptual phase. Herein, we chose diabetic wound as a representative injury model to explore the actual therapeutic results of tissue injury by injectable hypoxiainduced hydrogels. To enhance recovery and widen applicability, the hypoxia-induced system was incorporated with a conductive network by an origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 68 publications
3
53
0
Order By: Relevance
“…This is mainly because gelatin itself can promote cell adhesion and proliferation. 34 At day 7, the OD value of the GelMA/ColMA hydrogel increased significantly, indicating that the addition of ColMA can better support cell proliferation and growth, which was consistent with the results of live/dead staining. This is mainly due to the good biocompatibility of collagen and the highly porous structure of the hydrogel, which can promote cell proliferation.…”
Section: Resultssupporting
confidence: 85%
“…This is mainly because gelatin itself can promote cell adhesion and proliferation. 34 At day 7, the OD value of the GelMA/ColMA hydrogel increased significantly, indicating that the addition of ColMA can better support cell proliferation and growth, which was consistent with the results of live/dead staining. This is mainly due to the good biocompatibility of collagen and the highly porous structure of the hydrogel, which can promote cell proliferation.…”
Section: Resultssupporting
confidence: 85%
“…With regard to its role in tissue regeneration and wound healing, a vanillin-enriched hydrogel was used to treat mesenchymal stem cells derived from the adipose tissue of diabetic rats and upregulated the expression of markers of vascular regeneration, collagen deposition, and hair follicle reconstruction [ 83 ]. In another study, the application of vanillin-supplemented chitosan membranes on skin incisions in diabetic rats reduced the wound size and TNF-α and IL-1β levels, increasing re-epithelialization, angiogenic stimulus, and collagen deposition [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…Conductive hydrogel has been employed as scaffold for the treatment of diabetic wounds. Jin et al recently reported a 1 3 conductive hydrogel scaffold based on AT, hyaluronic acid and gelatin [184]. Compared with nonconductive hydrogel, the conductive hydrogel was found to upregulate the level of Cx43, owing to better transport of molecules and ions between cells.…”
Section: Hydrogelmentioning
confidence: 99%